Rancangan Dan Simulasi Alat Pemotong Bata Ringan Gerak Horizontal - Ardiansyah, Rizki; Rodika, Rodika; Idiar, Idiar (Jurnal Inovasi Teknologi Terapan, 2026)
This research aims to design and simulate a Hebel-type lightweight brick cutting machine with a horizontal motion system to improve cutting efficiency and precision at the TACON Tangan Construction production house in Bangka Belitung. The development of this tool is based on the needs of small industry players to increase productivity and reduce production costs, because most of the cutting process is still done manually. The design uses the VDI 2222 method which includes the planning, concept development, technical design, and design completion stages. This machine works with an electric motor transmission system that drives the cutting wire through an eccentric shaft, resulting in horizontal reciprocating motion. Simulation results using SolidWorks show that the machine works stably, efficiently, and safely. The design considers aspects of ergonomics, safety, and ease of maintenance. Theoretically, this design can increase cutting effectiveness by up to 40% and support the productivity of lightweight brick manufacturing.